Implementation of Single Moving Average Method for Fashion Forecasting - Musthofa Br. Butar-Butar, Yulia Syahfitri; Helmiah, Fauriatun; Syahputra, Abdul Karim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Toko Mazaya is a business engaged in the sale of clothing, celada and bags. During its sales, there is often a shortage or accumulation of the number of products to be marketed, not in accordance with the number of requests from customers, there is no computerized system for trading. This research aims to implement the single moving average method for forecasting the stock of products to be provided to support proper decision making. By using historical sales data from January 2024 to January 2025 to forecast 6 month ahead. the results of forecasting clothes for the next 6 months to July 2025 with the smallest MAPE level of 9.52 in May 2025 with a forecast amount of 55. While the results of pants forecasting for the next 6 months to July 2025 with the smallest MAPE level of 9.41 in June 2025 with a forecast amount of 47.50 and the results of bag forecasting for the next 6 months to July 2025 with the smallest MAPE level of 8.89 in February 2025 with a forecast amount of 40.00.